2019
DOI: 10.1111/aphw.12172
|View full text |Cite
|
Sign up to set email alerts
|

Making New Year's Resolutions that Stick: Exploring how Superordinate and Subordinate Goals Motivate Goal Pursuit

Abstract: Background New Year's Eve is a time when people make resolutions, but, more often than not, fail to achieve them. Previous research highlighted the positive effect of subordinate goals in goal pursuit. We argue that combining superordinate and subordinate goals contributes to successful goal pursuit, especially in the long run. We test whether a simultaneous focus on both goal types helps people to keep their resolutions. Methods Using a 2 × 2 between‐subjects design, participants (N = 256) formulated a resolu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 35 publications
0
17
0
Order By: Relevance
“…Based on prior research (Freund & Hennecke, 2012; Freund et al, 2010; Gillison et al, 2015; Hennecke & Freund, 2014; Höchli et al, 2019; Kitsantas et al, 2004; Pham & Taylor, 1999), we expected that the process‐focused (vs. outcome‐focused) program would yield better behavioral outcomes and more positive subjective experiences during the workout challenge. However, findings from the present study suggest that the relative effects of a process‐focused (vs. outcome‐focused) weight loss intervention may not be as straightforward as expected.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Based on prior research (Freund & Hennecke, 2012; Freund et al, 2010; Gillison et al, 2015; Hennecke & Freund, 2014; Höchli et al, 2019; Kitsantas et al, 2004; Pham & Taylor, 1999), we expected that the process‐focused (vs. outcome‐focused) program would yield better behavioral outcomes and more positive subjective experiences during the workout challenge. However, findings from the present study suggest that the relative effects of a process‐focused (vs. outcome‐focused) weight loss intervention may not be as straightforward as expected.…”
Section: Discussionmentioning
confidence: 99%
“…Freund and colleagues (2010) found that those with goals to exercise regularly reported more positive affective experiences, and increases in perceived goal attainability, involvement, and satisfaction when focusing on the process (vs. outcome) of goal pursuit. Other studies have found that individuals who focus on the process of goal pursuit have higher perceived success (Freund & Hennecke, 2012;H€ ochli et al, 2020 and improvements in self-efficacy for goal-relevant behaviors (Gillison et al, 2015). Taken together, process-versus outcome-focused interventions may foster more positive subjective experiences, which can contribute to sustained motivation for behavior change (Baldwin et al, 2006).…”
Section: Evidence For Process-focused Interventionsmentioning
confidence: 99%
See 2 more Smart Citations
“…While efficacious, this approach may not effectively reach the large segments of the population who gain weight during the winter holiday season [2]. The start of the calendar year is widely recognized as a critical time window to support the adoption of healthy behaviours [7,8]. Strategies that can capitalize on this motivation and encourage healthy behaviours could potentially counter the consequences of unhealthy behaviours over the winter holidays [7,9].…”
Section: Introductionmentioning
confidence: 99%